2017
DOI: 10.1089/jpm.2016.0541
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Efficacy of Trigger Point Injection in Advanced Cancer Patients

Abstract: The TPI efficacy is likely high when advanced cancer patients have fewer MTrPs together with cancer pain at areas other than the lower back or hip. MTrPs in advanced cancer patients are more commonly observed together with cancer pain rather than independently. Healthcare providers should recognize the relationship between MTrP and cancer pain and proactively perform physical examinations to detect MTrPs for potential TPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
14
0
2
Order By: Relevance
“…These results were consistent with those of a previous study (6). Of the enrolled patients, the percentage of patients who met diagnostic criteria for MPS was 43.6%, which is within the range of 31-45% reported in previous studies (4)(5)(6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were consistent with those of a previous study (6). Of the enrolled patients, the percentage of patients who met diagnostic criteria for MPS was 43.6%, which is within the range of 31-45% reported in previous studies (4)(5)(6).…”
Section: Discussionsupporting
confidence: 92%
“…MPS is found in 31-45% of cancer patients who complain of pain (4)(5)(6). One of the reference criteria of the MPS diagnostic criteria is that pain worsens with stress (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, two randomized controlled trials reported that manual pressure release of TrPs provided no additional beneficial effects to a standard physical therapy program for upper limb pain and function following breast cancer surgery. In 2017, Hasuo et al reported that TrPs in advanced cancer patients are more commonly observed together with cancer pain rather than independently (Hasuo et al, 2017). This review highlights the importance of a comprehensive evaluation that includes the presence of MPS in patients presenting with a history of either head and neck cancer or breast cancer.…”
Section: Reviewsmentioning
confidence: 94%
“…The efficacy of myofascial trigger point injections in patients with advanced cancer was evaluated in two studies, demonstrating decreased spontaneous and pressure-evoked pain [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%